A reappraisal of the Cenozoic stratigraphy of the Malay and West Natuna Basins. Issue 5 (1st June 2021) - Lunt, Peter
Abstract: This review emphasizes that much geological data has a context, and properties of quality (reliability, precision) that are sometimes overlooked. A review of a pair of wells is e-appraised to examine the lithostratigraphic formations and seismostratigraphic "Groups" commonly used to describe Malay Basin Cenozoic stratigraphy. A new interpretation of the wells helps to develop an objective, genetic stratigraphic framework. Such an evidence-based framework is superior to both the old formation concepts, and the seismostratigraphic horizons, neither of which are part of a predictive facies model that allowed testing, or integration with other stratigraphic disciplines. The tectono-stratigraphic framework that is described here correlates very well with regional tectonic models. It also appears to have no link to eustatic sea-level changes until the mid-Pliocene, after which a strong glacio-eustatic signal is observed. The new inductive model asks fundamental questions about the deposition and palaeographic distribution of an important oil reservoir (the J Sand, Lower Ledang Sand, or Pasir Sandstone). It also questions how we should interpret seismic, and how we should replace idealised (deductive) models with evidence-based methods. As exploration in a mature area relies on subtle plays with stratigraphic components it is essential to have a tested and scientifically defendable stratigraphic framework.